Implementation of clean and healthy living behavior (PHBS) in mobilizing public awareness to create a clean and healthy village in Ngaropoh Hamlet - Prasojo Pribadi; Farida Farida; Aninda Tri Yuliasari; Widya Krisna Murti; Asmaul Husna; Indriatri Septidaryanti (Community Empowerment, 2023)
Implementation of clean and healthy living behavior (PHBS) is an effort to empower household members to understand, want, and be able to practice clean and healthy living behaviors in the community. The purpose of this community service is to increase public understanding of clean and healthy living behavior and improve public health standards. The participants of this activity is the residents of Ngaropoh Hamlet. The method used is the participatory rural appraisal (PRA) approach with socialization, education and training about PHBS, planting medicinal plants, the Covid-19 vaccine, and self-healing, and cadre assistance. The resulting impact is that people understand, aware, and implement clean and healthy behavior in their environment. In the future, it is hoped that the residents of Ngaropoh Hamlet will remain consistent in maintaining a clean and healthy lifestyle.